Consumer behavior and payment choice: 2006 conference summary - Margaret Carten; Dan Littman; Scott Schuh; Joanna Stavins (Federal Reserve Bank of Boston, 2007)
This paper summarizes the proceedings of the second Consumer Behavior and Payment Choice conference, held at the Federal Reserve Bank of Boston on July 2527, 2006. These conferences are unique in featuring the collaboration of two groups of payments experts the private-sector payments industry on the one hand, and the academic, research, and policymaking communities on the other to stimulate more research and understanding of consumer payment behavior. The central focus of this second conference was learning more about the numerous consumer payments data sources that are available but which are not well known or easily accessed, often for proprietary reasons and discovering what further information is needed. Panel sessions on payment card loyalty programs and the transition from cash to electronic payments were informative and stimulated much debate. Research paper presentations provided additional support for the collection and analysis of innovative new data sources to enhance our understanding of the decisions consumers make when choosing payment methods.
Keywords: D11; D12; E21; E41; G28; G11; 330; Zahlungsverkehr; Bargeldloser Zahlungsverkehr; Konsumentenverhalten; USA